A review of tissue engineering in regenerative endodontic treatment - Prasetyo, Eric Priyo; Wahjuningrum, Dian Agustin; Sampoerno, Galih; Sukandar, Wilson; Shariz Bin Sharizal, Shafy; Paidal, Nurfahira; Fadiyan Amriel, Menza; Gunawan, Nathania Elita; Suardita, Ketut; Tjendronegoro, Evelyn (Conservative Dentistry Journal, 2024)
Background: Regenerative endodontic treatments are classified based on approach in the procedures and principles. One is cell-free approach that involves a revitalization procedure to achieve continued root growth while the other is cell-based approach which involves pulp/dentin regeneration through isolation and ex vivo expansion of stem cells seeded in the scaffold and then transplanted into the canal space. Technically, the cell-free approach is simpler than cell-based approach because the former does not concern about external stem cell isolation and culture. Currently, the gold standard and the one that has been clinically performed is cell-free approach. Cell-based approach is still not a standard because currently the cell-based approach is still in the clinical trial stage. Purpose: to evaluate the biological basis and clinical protocols recently used in regenerative endodontic treatment and discuss potentially future treatment approaches. Review: The literature review was searched in PUBMED with the keywords: immature permanent teeth, pulp revascularization, stem cells and regenerative endodontics. The regenerative endodontic treatments with various procedures and techniques result in a significant increase in root length and dentinal wall thickness. Stimulation of stem cells in apical root canal system is required to induce tissue formation and continued root maturation. Conclusion: The success of regenerative endodontic therapy relies on the development of a technique that enables clinicians to create functional pulp tissue within cleaned and shaped root canal systems. It is hoped that further research studies are required to define advantages and limitations of cell-free and cell-based approach.